Pedagogical system as a subject of scientific research - Proshkin, Volodymyr (Continuing Professional Education: Theory and Practice, 2023)
An article deals with such terms as “system”, “systematic approach”, “systems’ general theory”. Historical excursus according to formation of systematic approach in scientific researches has been carried out. The main requirements to description of pedagogical system and its peculiarities have been specified. They are complicated and dynamic so they function within changes of different characteristics of external environment; pedagogical systems are purposeful systems that have relative independence of external environment and surroundings). It has been pointed out that a structure of the system is made of definite elements (components) and also connection between them. The typical structure of the pedagogical system has been represented. It is a target component (aim, task, result); a subject and object component (teachers and students cooperate within a context of the research); a content component (forms and methods of pedagogical process); a technological component (pedagogical technology of realization different forms and methods of pedagogical process). It is figured out that pedagogical system specificity consists of its structure which is able to be not only self-made but also supplemented by authors according to the specification of the research work. Motivation and incentive component has been used in pedagogical system of integration research and educational work in future teachers’ training. It has been considered as the most important way to effective cooperation of all the others pedagogical system components and also a creation of positive students’ motivation to research work. Consequently science acquires a special significance for future teachers, secure interest’s stableness to it as a professional-oriented necessity. Principles, structure peculiarities and realization of pedagogical system have been singled out.